Historicism in Max Weber - Campos, Daniel Vasconcelos (Universidade Estadual Paulista / UNESP, 2012)
This article deals with Max Weber’s theory of cultural sciences. It aims at discussing on his place in humanities methodological dispute. More than a broad subject, the concept of cultural sciences provides us a guiding thread to understand his historical approach. History emerges as a basic part in his project to develop a non-philosophical, or scientific, critique of thinking.